Implementation of Morning Sermons in Building Self-Confidence in Female Students of Persada Students - Raisah Hani (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
Self-confidence is an important aspect of every individual that affects themselves and the surrounding environment. Many learning methods provide opportunities for students to increase their self-confidence, one of which is through the cultum program, especially in shaping self-confidence and communication when speaking in front of many people. The program held by the KH.Ahmad Dahlan Yogyakarta Student Boarding School with the morning cultum provides learning for female students in implementing religious values and forming self-confidence. This type of research is qualitative research with data collected in the form of interviews, observation and documentation. The results showed that the santriwati of the KH. Ahmad Dahlan Yogyakarta Student Boarding School succeeded in forming self-confidence and the effective morning cultum could increase the self-confidence of the santriwati of the KH. Ahmad Dahlan Yogyakarta Boarding School marked by the existence of 4 important points that can be concluded, namely 1) personal experience, 2) observing experience (modeling), 3) social persuasion or motivation around and 4) regulation of stress against stage fright.